Influence of cellulose fiber addition on self-healing and water permeability of concrete. (June 2020) - Singh, Harshbab; Gupta, Rishi
Abstract: Crack formation under tensile forces is a major weakness of concrete. Cracks make concrete vulnerable to extreme environment due to ingress of water and harmful compounds from surrounding environment. Even though concrete is susceptible to cracking it has ability to seal its cracks by itself to some extent due to autogenous self-healing. So far only few studies have been done on autogenous healing of fiber reinforced concrete. So, this study aims to evaluate the self-healing potential and water permeability of cellulose fiber reinforced concrete (CeFRC). The two types of composites; control and cellulose fiber reinforced concrete have been investigated. Compressive strength and flexural tests were performed to measure the mechanical properties of the composites, water permeability test was used to evaluate the coefficient of permeability and the self-healing performance was investigated by using ultrasonic pulse velocity (UPV) and a patented self-healing test. The results indicate that the water permeability coefficient decreased by 42 % whereas the healing ratio increased at a higher rate for the initial days of healing when cellulose fibers were added in the mix. CeFRC also results in a 7.8 % increase in the flexural strength and demonstrate a higher self-healing ratio based on the UPV test.